PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GO-KART DENGAN SISTEM KEMUDI LINKAGE PADA MATA KULIAH SISTEM CHASIS, KEMUDI, REM DAN SUSPENSI - Toto Wicaksono; Muhammad Priyo Permana (Journal of Automotive Technology Vocational Education, 2026)
This study aims to develop a go-kart-based learning media using a linkage steering system for the Chassis, Steering, Brake, and Suspension course and to determine its feasibility based on content suitability and design suitability. This research employed the research and development (R&D) method using the four-D (4D) development model consisting of Define, Design, Develop, and Disseminate stages. Data were collected through expert validation sheets and student response questionnaires using a Likert scale. Data were analyzed descriptively by converting the obtained scores into feasibility percentages. The results indicate that the developed go-kart learning media successfully represents the working mechanism of the linkage steering system and fulfills the requirements of vocational learning media. Expert validation showed that the developed media was categorized as highly feasible in terms of both content and design. Student responses also indicated that the media was very appropriate for practical learning activities. Therefore, the developed learning media is feasible to support learning activities in the Chassis, Steering, Brake, and Suspension course. Keywords: learning media, go-kart, linkage steering system, vocational education, 4D model.